PENGARUH PENAMBAHAN BAKTERI ASAM LAKTAT (BAL) ASAL WIKAU MAOMBO DAN LAMA FERMENTASI TERHADAP KARAKTERISTIK ORGANOLEPTIK MINUMAN PROBIOTIK GULA AREN - Aguswinarto, Aguswinarto Aguswinarto (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2016)
Yogurt is a fermented drink of milk through the activity of lactic acid bacteria (LAB) with a distinctive aroma and taste slightly acid formed by bacteria that break down the sugar in milk is lactose into lactic acid. The purpose of this study was to determine the effect of addition of LAB isolated from wikau maombo and fermentation time on the organoleptic characteristics of probiotic drink products made from palm sugar. The research study used a Randomized Complete Design (RCD) with two factors, concentration of adding LAB (1%, 3%, 5%) and fermentation time (8 hours, 16 hours, 24 hours). The results showed that the best treatment with organoleptic parameter is concentartion of 1% BAL and 16 hours fermented has liking for colour 3.78 (like), texture 3.63 (like), flavor 3.75 (like) and taste 3.78 (like).